Identifying the form of illocutionary acts generated by the teacher in the process of teaching in class VIII A SMP Negeri 1 Poso - Okvin Helfiana Manggeni; Novalita Tungka (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This research is to identify the illocutionary forms produced by the English teacher in class VIII A at SMP N 1 Poso during the teaching in class. Illocutionary speech acts are utterances expressed by the teacher as a speaker to the speech partner to take action according to what is conveyed. The purpose of the research is to find out the form of illocutionary speech produced by the English teacher when she was teaching in class. The research method used is the descriptive-qualitative method. The data in this research was taken from only English utterances generated by the English teacher. The instruments used in this study were a phone recording and field notes on the utterances spoken. The researcher herself identified and collected the data findings after listening to the recordings. The findings of the data indicate that there are three forms of illocutionary produced by the English teacher: 24 times directive, 10 times expressive, and 10 times assertive. Directive speech acts are more dominantly used by the English teacher when teaching in class because directive speech acts generated by the teacher have an impact on students, and they, as a speech partner, do what is said by the speaker. Directive speech can manage and control teaching activities between teacher and students, and the teacher as a speaker can ask questions to students to make them feel more motivated and active in learning English.